Meeting of Deputy Ministers Copenhagen, Denmark. May 27, 2010. Presentation about Sustaining Arctic Observing Networks (SAON). - Calder, John (2010)
Presentation about the Sustaining Arctic Observing Networks (SAON) initiative delivered at the first Deputy Ministers' Meeting of the Arctic Council held in Copenhagen, Denmark 27 May 2010.